2005
DOI: 10.1007/s10546-005-9022-8
|View full text |Cite
|
Sign up to set email alerts
|

Scintillometer-Based Turbulent Fluxes of Sensible and Latent Heat Over a Heterogeneous Land Surface – A Contribution to Litfass-2003

Abstract: Abstract. The performance of a combined large aperture scintillometer (LAS) and a millimetre wave scintillometer (MWS) for estimating surface fluxes of sensible and latent heat over natural landscape is investigated, using data gathered during LITFASS-2003. For this purpose the LAS-MWS system was installed in a moderately heterogeneous landscape over a path length of 4.7 km with an effective beam height of 43 m. The derived surface fluxes have been compared with aggregated eddy-covariance (EC) measurements. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
98
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(103 citation statements)
references
References 42 publications
5
98
0
Order By: Relevance
“…Furthermore Fig. 3 Figure 3, thus, corroborates the performance of the WagLAS and K&ZLAS09 found in the literature: the WagLAS has been shown to give accurate flux estimates (De Bruin et al 1995;Green 2001;Beyrich et al 2002;Meijninger et al 2002Meijninger et al , 2006, whereas the K&ZLAS has been shown to have systematic errors of up to 20% (Kleissl et al 2008(Kleissl et al , 2009). In the following we therefore use the WagLAS as the reference scintillometer.…”
Section: Comparison Of H Ec With H W Agl As and H K Andz L As09supporting
confidence: 86%
“…Furthermore Fig. 3 Figure 3, thus, corroborates the performance of the WagLAS and K&ZLAS09 found in the literature: the WagLAS has been shown to give accurate flux estimates (De Bruin et al 1995;Green 2001;Beyrich et al 2002;Meijninger et al 2002Meijninger et al , 2006, whereas the K&ZLAS has been shown to have systematic errors of up to 20% (Kleissl et al 2008(Kleissl et al , 2009). In the following we therefore use the WagLAS as the reference scintillometer.…”
Section: Comparison Of H Ec With H W Agl As and H K Andz L As09supporting
confidence: 86%
“…The combination of a (near-infrared) LAS and a (94-GHz) microwave scintillometer (known as the two-wavelength method) makes it possible to determine the fluxes of sensible heat and latent heat directly at scales of several kilometres from the path-averaged structure parameter data (C n 2 ) applying similarity relationships (Meijninger et al 2002. A footprint analysis of the setup performed by Meijninger et al (2006) showed that more than 85% of the source area of the scintillometers represents farmland (for all wind directions).…”
Section: Scintillometer and Airborne Measurementsmentioning
confidence: 99%
“…The reliability of scintillometers to provide accurate estimates on surface fluxes has been proven in many different natural or semi-natural areas (e.g. Thiermann and Grassl 1992;Green et al 1994;De Bruin et al 1995;Beyrich et al 2002Beyrich et al , 2012Meijninger et al 2006;Ezzachar et al 2007;Evans et al 2012;Samain et al 2012).…”
mentioning
confidence: 99%